2020
DOI: 10.1093/femspd/ftaa026
|View full text |Cite
|
Sign up to set email alerts
|

The pathological autopsy of coronavirus disease 2019 (COVID-2019) in China: a review

Abstract: The coronavirus disease 2019 (COVID-2019) that emerged in Wuhan, China, has rapidly spread to many countries across all six WHO regions. However, its pathobiology remains incompletely understood and many efforts are underway to study it worldwide. To clarify its pathogenesis to some extent, it will inevitably require lots of COVID-2019-associated pathological autopsies. Pathologists from all over the world have raised concerns with pathological autopsy relating to COVID-2019. The issue of whether a person died… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 24 publications
7
58
0
1
Order By: Relevance
“…Lung sections from the two HIS-DRAGA survivors of SARS-CoV-2 infection were further analyzed to characterize pathological changes. As in recent reports based on human autopsies [57][58][59] , the H&E and Mason-trichrome staining of lung sections showed heavy parenchymal infiltrates around the large bronchioles and at peripheral areas of the lungs, as well as hCD45 + cells and human (CD3 + ) T cells dispersed throughout the lung parenchyma, which were more pronounced in the mouse infected with the high dose of virus ( Fig. 5).…”
Section: Sars-cov-2 Infected His-draga Mice Display Human-like Lung Isupporting
confidence: 82%
See 1 more Smart Citation
“…Lung sections from the two HIS-DRAGA survivors of SARS-CoV-2 infection were further analyzed to characterize pathological changes. As in recent reports based on human autopsies [57][58][59] , the H&E and Mason-trichrome staining of lung sections showed heavy parenchymal infiltrates around the large bronchioles and at peripheral areas of the lungs, as well as hCD45 + cells and human (CD3 + ) T cells dispersed throughout the lung parenchyma, which were more pronounced in the mouse infected with the high dose of virus ( Fig. 5).…”
Section: Sars-cov-2 Infected His-draga Mice Display Human-like Lung Isupporting
confidence: 82%
“…route with non-mouse-adapted SARS-CoV-2, sustaining the infection for at least 14 days, and that they can develop severe human-like lung immunopathology, including T-cell infiltrates, alveolar damage and microthrombi. As in recent analyses of human autopsy samples from COVID-19 patients [57][58][59] , the lung infiltrates of infected DRAGA mice were intra-parenchymal, relatively diffuse, and grouped around terminal bronchioles and at the periphery.…”
Section: Discussionsupporting
confidence: 58%
“…1 Specially, striking lesions observed in vessels, both lymphocytic vasculitis, and the hyalinosis of the arteriolar wall. 27 However, all of them were negative in RT-qPCR tests for SARS-CoV-2 using nasopharyngeal and rectal samples. These results agree with a large-scale study that recently has been shown to assess SARS-CoV-2 infection in 817 companion animals living in northern Italy and neither animals tested positive using RT-qPCR were found.…”
Section: Discussionmentioning
confidence: 96%
“…At the renal level, however, intact glomeruli and acute renal tubular damage have been documented. With anti-COVID-19 antibodies localized only to the renal tubular cells of the tissues infected by immunohistochemical staining [ 70 ]. Additionally, COVID-19 viral nucleocapsid protein antigen, cell apoptosis and proinflammatory cytokine expression have been documented in the spleen and lymph nodes of autopsies of infected subjects.…”
Section: Autopsy Findingsmentioning
confidence: 99%